2016
DOI: 10.1002/jat.3359
|View full text |Cite
|
Sign up to set email alerts
|

Gender and geographical variability in the exposure pattern and metabolism of deoxynivalenol in humans: a review

Abstract: Deoxynivalenol (DON, also known as vomitoxin) is a common mycotoxin found worldwide, especially in contaminated food. DON is toxic to a variety of cells and tissues in humans. Three kinds of conjugated products (DON-3-glucuronide, DON-15-glucuronide and DON-7-glucuronide) can be found as major metabolites in human urine. Females and males show different patterns of exposure levels, and human exposure to DON also shows some geographical differences because of different DON levels in cereal-based foods, food int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 80 publications
(140 reference statements)
3
22
0
Order By: Relevance
“…Using recombinant human UGTs, it was demonstrated that DON-15-GlcA is predominantly produced by UGT2B4 and DON-3-GlcA by UGT2B7, one of the most important hepatic UGTs . Both enzymes occur in different variants in Caucasian, Hispanic, African, and Asian populations (Guillemette 2003), which might be one reason for the observed geographical variability in DON metabolism (Chen et al 2016). However, considering this diversity, the data on animal and human DON glucuronides from different reports are astonishingly congruent, and were also confirmed in this study by our in vitro and in vivo experiments.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Using recombinant human UGTs, it was demonstrated that DON-15-GlcA is predominantly produced by UGT2B4 and DON-3-GlcA by UGT2B7, one of the most important hepatic UGTs . Both enzymes occur in different variants in Caucasian, Hispanic, African, and Asian populations (Guillemette 2003), which might be one reason for the observed geographical variability in DON metabolism (Chen et al 2016). However, considering this diversity, the data on animal and human DON glucuronides from different reports are astonishingly congruent, and were also confirmed in this study by our in vitro and in vivo experiments.…”
Section: Discussionsupporting
confidence: 85%
“…The hepatic glucuronidation pattern of DON varies between species, which has been shown consistently in in vivo Schwartz-Zimmermann et al 2017) and in vitro Uhlig et al 2016) studies. In addition, there are differences related to sex, age, health status, diet, or environment Chen et al 2016). The DON-metabolising UGTs belong to an enzyme superfamily that is found ubiquitously in living organisms and has a widely ranging spectrum of endogenous and exogenous substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Human biomonitoring in combination with dietary surveys can be a useful tool to confirm exposure of mycotoxins, to correlate exposure to certain food intake and to perform trend analyses. In addition, it can be an important tool to reveal influence of other factors such as differences in exposure due to socioeconomic or regional factors (Ali et al 2016;Breitholtz et al 1991;Chen et al 2017;Mitropoulou et al 2018;Pacin et al 2008). However, despite those benefits, human biomonitoring is more useful in human health and dietary studies, than its use in exact exposure assessment of daily intake.…”
Section: Introductionmentioning
confidence: 99%
“…They can infect small grain cereals such as wheat, oat, barley and maize (Nganje, Kaitibie, Wilson, Leistritz, & Bangsund, ), which results in harmful contamination and decreased yields (Ferrigo, Raiola, & Causin, ). Products, particularly those that are rich in carbohydrates, are attractive for the fungi development (Chen et al, ). Some species of Fusarium can exist together and usually more than one species is detected in probes.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, some of the aspects to consider are dietary differences, food processing and socioeconomic conditions of living (Marin, Ramos, Cano-Sancho, & Sanchis, 2013). For example, the differences in DON exposure are based on food intake in different geographical areas (Chen et al, 2017).…”
mentioning
confidence: 99%